Metagenomic Insight into the Microbiome and Virome Associated with Aedes aegypti Mosquitoes in Manado (North Sulawesi, Indonesia) - Janno Berty Bradly Bernadus; Jantje Pelealu; Grace Debbie Kandou; Arthur Gehart Pinaria; Juliet Merry Eva Mamahit; Trina Ekawati Tallei (MDPI AG, 2023)
The aim of this study was to investigate the microbial diversity encompassing bacteria, fungi, and viruses within the composite microbial community associated with Aedes aegypti mosquitoes in Manado, Indonesia, using a whole-genome shotgun metagenomics approach. Female mosquitoes were collected and grouped into pools of 50 individuals, from which genomic DNA (gDNA) and RNA were extracted separately. Whole-genome shotgun metagenomics were performed on gDNA samples. The bioinformatics analysis encompassed quality assessment, taxonomic classification, and visualization. The evaluation of the microbial community entailed an assessment of taxa abundance and diversity using Kraken version 2.1.2. The study delineated the prevalence of dominant bacterial phyla, including Proteobacteria, with varying abundance of Firmicutes, Bacteroidota, and Actinobacteria, and notable occurrence of Tenericutes. Furthermore, the presence of the fungal phylum Ascomycota was also detected. Among the identified barcodes, Barcode04 emerged as the most abundant and diverse, while Barcode06 exhibited greater evenness. Barcode03, 05, and 07 displayed moderate richness and diversity. Through an analysis of the relative abundance, a spectrum of viruses within Ae. aegypti populations was unveiled, with Negarnaviricota constituting the most prevalent phylum, followed by Nucleocytoviricota, Uroviricota, Artverviricota, Kitrinoviricota, Peploviricota, Phixviricota, and Cossaviricota. The presence of Negarnaviricota viruses raises pertinent public health concerns. The presence of other viral phyla underscores the intricate nature of virus-mosquito interactions. The analysis of viral diversity provides valuable insights into the range of viruses carried by Ae. aegypti. The community exhibits low biodiversity, with a few dominant species significantly influencing its composition. This has implications for healthcare and ecological management, potentially simplifying control measures but also posing risks if the dominant species are harmful. This study enriches our comprehension of the microbiome and virome associated with Ae. aegypti mosquitoes, emphasizing the importance of further research to fully comprehend their ecological significance and impact on public health. The findings shed light on the microbial ecology of Ae. aegypti, offering potential insights into mosquito biology, disease transmission, and strategies for vector control. Future studies should endeavor to establish specific associations with Ae. aegypti, elucidate the functional roles of the identified microbial and viral species, and investigate their ecological implications.